2015
DOI: 10.1027/0269-8803/a000136
|View full text |Cite
|
Sign up to set email alerts
|

Body Position Influences Cardiovascular Disgust Reactivity

Abstract: It has been suggested that elevated trait disgust constitutes a vulnerability factor for fainting episodes. We tested the hypothesis that disgust-prone individuals are susceptible to vasovagal syncope by means of a tilt table experiment, during which 30 women were presented with disgusting pictures in a supine and a 70° upright position. The results showed that relative to disgust elicitation in the supine position, tilting reduced diastolic blood pressure during disgust elicitation, which could indicate incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The majority of studies have observed a heart rate deceleration during disgust provocation [20,21,22,23]. Nevertheless, other studies have reported heart rate accelerations associated with exposure to disgusting stimuli [24,25,26]. Moreover, it has been suggested that the physical dimension of disgust elicits enhanced activity of the parasympathetic nervous system (increased HRV), whereas heart rate does not show any changes [27].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies have observed a heart rate deceleration during disgust provocation [20,21,22,23]. Nevertheless, other studies have reported heart rate accelerations associated with exposure to disgusting stimuli [24,25,26]. Moreover, it has been suggested that the physical dimension of disgust elicits enhanced activity of the parasympathetic nervous system (increased HRV), whereas heart rate does not show any changes [27].…”
Section: Introductionmentioning
confidence: 99%
“…The sum of these phenomena is thought to serve as a compensatory mechanism to stabilize potentially harmful arterial pressure. These findings also call attention to the interesting relationship between HR and potential immunity from pathogen threats (Schienle et al, 2015). For example, during times of non-chronic stress, the sympathetic nervous system can elevate HR and release neurotransmitters that bind to receptors on the surfaces of various immune cells that result in enhanced immune responses (Kenney & Ganta, 2014).…”
mentioning
confidence: 96%
“…Emotional stimuli such as disgust have been found to greatly influence HR (Schienle et al, 2015). Schienle and colleagues (2015) carried out a tilt-table study that had disgust-sensitive women shown disgusting pictures in both a 70° upright position and a supine position (Schienle et al, 2015). They found that while experiencing disgust in an upright tilted position, diastolic blood pressure drops, leading to potential lightheadedness and fainting spells.…”
mentioning
confidence: 99%
See 2 more Smart Citations